Pengembangan LKS Berbasis Pendekatan Scientific untuk Pembelajaran Geometri Materi Bangun Datar di Kelas III SDN NO. 34/1 Teratai Muara Bulian - S Sofnidar; Gustia Murni (Jurnal Gentala Pendidikan Dasar, 2016)
The purpose of this study was to develop a sheet of student activities with a Scientific approach to flat-woke material in class III SDN No. 34/1 Muara Bulian Lotus which has good validity according to experts and to determine the effectiveness of using student activity sheets on student learning outcomes. This type of research is development research. The instruments used in this study were expert assessment questionnaires for evaluation of teaching materials and assessment questionnaires for the design of student activity sheets with the Scientific approach, teacher and student responses questionnaire and student learning outcomes tests. From the results of the analysis carried out on the final test obtained 81.48% of the students reached KKM, the results of observation of student activities in the learning process reached 74.6%. This means that the student activity sheet made is in accordance with the purpose of the effectiveness of using the student activity sheet. So that this student worksheet can be used by elementary math teachers especially in flat learning.